Arc-bridge polydimethylsiloxane grafted graphene incorporation into quaternized poly(styrene-b-isobutylene-b-styrene) for construction of anion exchange membranes. (26th August 2019) - Mo, Zhao-Hua; Wu, Yi-Xian
Abstract: A novel robust quaternized poly(styrene- b -isobutylene- b -styrene) (QSIBS)-based anion exchange membrane (AEM) could be achieved via quaternization and cross-linking reaction of chloromethylated SIBS with amines in the presence of graphene sheets grafted with polydimethylsiloxane arc-bridges (G -g-Arc PDMS). The resulting cross-linked QSIBS/G- g - Arc PDMS composite membranes exhibit significantly high ion conductivity (σ) and dynamic mechanical properties, marked by low methanol permeability, together with improved chemical stability. The σ of composite AEM with 0.25 wt% of graphene loading reached remarkably to 1.81× 10 −2  S cm −1 at 60 °C, compared to that (1.15× 10 −2  S cm −1 ) of QSIBS. This membrane also behaves high storage modulus of 236 MPa even at 150 °C, while Nafion 115 lost its modulus at 150 °C. The homogeneous dispersion of G -g-Arc PDMS in QSIBS matrix leads to a great decrease in methanol permeability to 3.81× 10 −7  cm 2  s −1, which is much lower than that of Nafion 115. Graphical abstract: Image 10000 Highlights: A novel robust cross-linked SIBS/graphene sheets grafted with PDMS arc-bridges composite anion exchange membranes were prepared. The dispersed PDMS arc-bridges leads to high conductivity to 1.81×10 −2  S cm −1, low methanol permeability to 3.81×10 −7  cm 2  s −1 . The cross-linked membranes behave high storage modulus of 236 MPa even at 150 °C.